Self-Medication Practice, Attitude, and Knowledge of Health Science Students in Indonesia: A Cross Sectional Study - M. Shofwan Haris; Baiq Risky Wahyu Lisnasari (Pharmaceutical Journal of Indonesia, 2024)
Self-medication is a term to describe an act of using medication, whether traditional or synthetic, for self-treatment. This study was carried out to determine the pattern, attitude, and knowledge of self-medication among health science major students in Bangkalan, Indonesia. This cross-sectional study was conducted from May to June 2023. Data was obtained through self-administered questionnaire and the results expressed as percentages. This study enrolled 204 students from different majors, i.e. pharmacy (39.5%), nurse (33%), midwifery (17.9%), medical record science (9.1%), and others (3%). All of the participants have practiced self-medication in the last six month, at least once. The most common reason for self-medication were the mildness of the diseases (50%), the urgency to relieve symptoms fast (13%), and previous medical knowledge (13%). Multivitamin (42.2%) and analgesics (35.8%) were the most frequent used drugs for self-medication. The students tend to have positive attitude favoring self-medication. The majority (72.55%) of students demonstrated good level knowledge of self-medication. An effort to raise public awareness of the disadvantage of self-medication and the responsible way to practice it should continuously be made. The pharmacist should actively contributed in raising public awareness and more education should be given to the students regarding the risk of self-medication.